KELOMPOK TEMAN SEBAYA DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF SISWA SMPN 1 SIDOARJO - Tri Ahmad Budi Susilo (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
The focus of this study was to determine the effect of peer group variables and the use of social media on student consumptive behavior at SMPN 1 Sidoarjo. The type of research chosen is explanatory or explanatory research. The selected population coverage is 9 classes containing 297 students. The sampling method used was random or simple random sampling. The total sample selected was 30 students with data collection steps using a questionnaire instrument. The results of multiple regression analysis showed that the variable peer group and the use of social media showed a significant influence on the consumer behavior variable. Hypothesis testing explains that there is an influence generated by peer group variables and the use of social media on students' consumptive behavior separately (partially) or simultaneously (simultaneously). The results of calculating the multiple regression coefficients that show the contribution or contribution of the influence of peer group variables and the use of social media on the consumer behavior variable are quite high.